Virtual Influencers and Consumer Engagement in Indonesia: Extending the Technology Acceptance Model - Agung Wijoyo; Rodhiah Rodhiah; Muhardi Muhardi; Tasya Aspiranti (International Journal of Management Science and Application, 2026)
This research investigates the Indonesian consumers’ adoption of Virtual Influencers (VIs) by extending the technology acceptance model (TAM) through the integration of relational constructs. This study examined the effect of perceived usefulness (PU) and perceived ease of use (PEOU) on attitude, the effect of attitude on behavioural intention (BI) and the mediating role of trust in consumer engagement. Data were collected through an online survey from 500 Indonesian social media users aged 18–35 years old who actively follow VIs on Instagram or TikTok. The analysis used structural equation modeling (SEM) using SmartPLS and AMOS. Reliability and validity were measured by using Cronbach's alpha, composite reliability, AVE, and discriminant validity, while the mediation analysis was tested by bootstrapping with 5,000 resamples. The results show that PU and PEOU significantly affect attitudes, which in turn affect behavioral intention. Behavioral intention is also a significant factor in the development of trust, and trust is found to be the strongest predictor of engagement. In addition, cultural aspects such as collectivism and religiosity are discussed as contextual factors. The model has good explanatory power with R2 of 0.42-0.56. The results show that trust is a significant element in the intention-to-engagement process in the context of VIs. Practically, brands can prioritize transparency and cultural relevance when developing virtual influencers to increase engagement among Indonesian Millennials and Gen Z. This study contributes to the limited empirical literature on VIs in Southeast Asia by extending TAM with trust and engagement.